A study on imagery ability, flow experience and player satisfaction in table tennis - Wang, M. Y.; Chang, H. L.; Lee, K. C.; Huang, C. C. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
The objective of the study is to discuss the correlation between imagery ability, flow experience and satisfaction in table tennis. It takes players from institutes of higher education as subjects and gets 212 results by convenience sampling. The method to carry out this study is using the factor analysis, canonical correlation analysis and multiple stepwise regression analysis. ability and flow experience are in significantly positive correlation. Furthermore, the satisfaction can be predicted by imagery ability (imagery, target image) and flow experience (concentration, self-efficacy, self- accomplishment). To sum up, the significant conditions of satisfaction for players are imagery ability and flow experience. Hope the study raises player s` training satisfaction and enhances the performance on players and coaches.